2011
DOI: 10.1097/prs.0b013e318200afbf
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Postoperative Complications for Superficial Liposuction: A Review of 2398 Cases

Abstract: Superficial liposuction has potential risks for higher complications compared with conventional suction techniques, especially postoperative contour irregularity, which can be minimized with proper selection of candidates for the procedure, avoiding overzealous suctioning of superficial layer, and using a combination of ultrasound energy techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 24 publications
0
56
0
8
Order By: Relevance
“…Minor deficiencies in current fat-grafting include procedural complications and donor site morbidity (infection, bruising and seroma/hematoma) and in the longer term, scarring, and small contour deformities[64, 65]. More serious but rare complications include intravascular embolization that can lead to significant vascular occlusion including stroke[66] and pneumothorax infection, which has been described as a complication of fat grafting breasts[67].…”
Section: Discussionmentioning
confidence: 99%
“…Minor deficiencies in current fat-grafting include procedural complications and donor site morbidity (infection, bruising and seroma/hematoma) and in the longer term, scarring, and small contour deformities[64, 65]. More serious but rare complications include intravascular embolization that can lead to significant vascular occlusion including stroke[66] and pneumothorax infection, which has been described as a complication of fat grafting breasts[67].…”
Section: Discussionmentioning
confidence: 99%
“…Key words: body contouring; non-invasive body contouring; non-invasive fat reduction; laser fat reduction BACKGROUND Liposuction has been the most common modality [1] for fat reduction and body contouring, but associated risk included post-operative morbidity, recovery, and downtime [2]. Alternative or adjunctive methods for localized fat destruction such as lasers [3], high-intensity focused ultrasound [4,5], radiofrequency devices [6], and selective cryolipolysis [7,8,9,10,11] are increasingly being utilized to reduce downtime.…”
mentioning
confidence: 99%
“…In terms of harvest technique safety, they contend that “the harvest of ADSCs is generally associated with better patient acceptance.” They do not provide, however, any citations to support this claim. This is in stark contrast to the published evidence we provide that supports bone marrow aspiration as being safer than lipoaspiration [10‐13]. On a further note regarding harvesting techniques, our opponents suggest that lipoaspiration “allows for a larger amount of injectate that is more desirable for multiple joint procedures.” This is a point that we find completely irrelevant to the clinical scenario in question, as we are treating a patient with unilateral knee osteoarthritis.…”
Section: Case Scenariomentioning
confidence: 57%
“…Though many purport that liposuction is the gentler procedure, the available data do not support this position. A literature review indicates the reported overall complication rate following liposuction to be 8.6%, with a major complication rate of 0.7% [2,3]. Conversely, the adverse event rate following bone marrow aspiration is 0.0007% [4].…”
Section: Case Scenariomentioning
confidence: 99%